Labour's foreign policy since 1951 - Vickers, Rhiannon (The Labour Party and the world, 2011)
This is the second book in a unique two-volume study tracing the evolution of the Labour Party's foreign policy throughout the 20th century to the present date.This is the first comprehensive study of the history of the Labour Party's worldview and foreign policy. It argues that Labour's foreign policy perspective should be seen not as the development of a socialist foreign policy, but as an application of the ideas of liberal internationalism.Volume Two provides a critical analysis of Labour's foreign policy since 1951. It examines Labour's attempts to rethink foreign policy, focusing on intr.